2011
DOI: 10.1002/jsfa.4462
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to define the sodium requirement of lactating dairy cows in a tropical environment

Abstract: Consumption of a daily ration formulated to contain the current Na requirement set by the NRC appears to provide too much Na for lactating cows under tropical conditions. A tentative value of 1.2 g kg(-1) DM is proposed as the Na requirement for dairy cows under tropical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The clinical observations of Na deficiency were associated with decreased salivary Na and increased salivary K concentrations, leading to a salivary Na/K ratio of <4.3, which is indicative of Na deficiency. 18 The current observations on salivary Na and K concentrations are in line with data reported by Thiangtum et al, 5 who reported that the salivary Na/K ratio decreased to 4.8 when a ration was fed containing 0.4 g Na kg −1 DM for 32 days. In the latter study, however, no clinical signs such as pica were observed.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The clinical observations of Na deficiency were associated with decreased salivary Na and increased salivary K concentrations, leading to a salivary Na/K ratio of <4.3, which is indicative of Na deficiency. 18 The current observations on salivary Na and K concentrations are in line with data reported by Thiangtum et al, 5 who reported that the salivary Na/K ratio decreased to 4.8 when a ration was fed containing 0.4 g Na kg −1 DM for 32 days. In the latter study, however, no clinical signs such as pica were observed.…”
Section: Discussionsupporting
confidence: 92%
“…The data clearly show that supplemental Na did not restore the salivary Na/K to values of >6 . This was unexpected as the highest level of supplementation was calculated to exceed (1.7 g kg −1 DM) the dietary requirement (1.2 g kg −1 DM) of lactating dairy cows in a tropical environment. The actual Na consumed was found to be 1.6 g kg −1 DM for the HNa group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations